Introduction - Héloïse Faucherre-Buresi; Marie Lucas (Laboratoire Italien)
The demology or “science of the people” that emerged in Italy in the early nineteenth century was distinguished from other European countries’ folklore studies by its strong focus on regional specificities. In the context of the country’s difficult unification, the study of the folk customs of the Mezzogiorno in particular gained in depth, at the same time when the “southern question” (that is to say all the debates linked to the perception of a “backwardness” in the development of the south of the country) was taking shape. Largely compromised with fascism and its racist exaltation of local traditions, this neo-science was the subject of a renewed approach by Antonio Gramsci. He developed a dynamic and critical interpretation of the ambivalent notions of “folklore” and “popular culture”. His reflections and those of Ernesto De Martino later, set within a theory of economic and political power relations, contributed to the renewal of Italian ethnology in the post-war period. This issue, at the crossroads of several disciplines, examines the transition from a romantic approach to the “popular soul” and picturesque customs to a Marxist-inspired political study of the cultures of subaltern groups.